Pharmacokinetics of cefodizime following single doses of 0.5, 1.0, 2.0, and 3.0 grams administered intravenously to healthy volunteers. - Lenfant, B (1995)
Cefodizime is a new expanded-spectrum cephalosporin for parenteral use which possesses a broad antibacterial spectrum and potent antibacterial activity and is stable against most beta-lactamases. The aim of this study was to assess the pharmacokinetics of cefodizime, administered intravenously, over the dose range of 0.5 to 3.0 g in healthy volunteers. Concentrations of cefodizime in the serum and urine were determined by high-performance liquid chromatography. The area under the concentration-time curve from 0 h to infinity and the amount of drug excreted in urine from 0 to 34 h increased in a linear, dose-dependent manner with increasing doses of antibiotic from 0.5 to 3.0 g. Mean concentrations of cefodizime in plasma at the end of infusion increased from 97 to 440 mg liter-1 over the dose range 0.5 to 3.0 g and displayed a slight deviation from linearity at doses in excess of 2.0 g. Total plasma clearance (3.11 liters h-1), volume of distribution at steady state (10.5 liters), terminal elimination half-life (3.3 h), and renal clearance (1.91 liters h-1) remained constant over the doses administered. Cefodizime was well tolerated in this study.